An Analysis of Hate Crime Victimization Amongst Immigrants - McCann, Wesley S. (American journal of criminal justice, 2022)
The primary purpose of the current study was to understand immigrant hate crime victimization in the U.S. Specifically, the authors analyzed the most recent data from the National Crime Victimization Survey to explore the factors that influence hate crime experiences and reporting by immigrant victims. Results from the binary logistic regression analyses revealed significant relationships between immigration status, citizenship status, number of prior incidents experienced as well as certain demographic characteristics and being the victim of a hate crime. Overall, being an immigrant or non-citizen, was associated with an increase in odds of being the victim of a hate crime. In terms of victims’ reporting of hate crime, immigration status had no impact, but the number of incidents experienced, being married and being less educated significantly increased reporting among victims. Numerous recommendations are provided, however, the most important step forward is the creation of a legal status category within the UCR’s Hate Crime data collection coupled with several legal protections for victims.